THE POTENTIAL OF MARINE CLAY USED FOR LANDFILL LINER: A GEOTECHNICAL STUDY - Zarime N..; Solemon B.; Yaacob W.Z.W.; Wahab W.A.; Omar R.C.; Isa A.A.M. (GEOMATE International Society, 2024)
The increase in excessive solid waste due to the rapid growth of the world's population is considered a severe environmental problem. The landfill leachate will contaminate groundwater, putting all living things at risk. Natural clay is a common liner material used to keep landfill leachate from polluting the environment. This study investigates the geotechnical properties of natural marine clay and its potential to be used as a landfill liner. To investigate the soil properties, the Sungai Besar marine clay (SBMC) was subjected to physico-chemical, morphology and mineralogy properties including particle size distribution, specific gravity, atterberg limits, compaction, permeability, pH, organic content, cation exchange capacity (CEC), specific surface area (SSA), X-Ray Diffraction (XRD) and scanning electron microscope (SEM). Batch Equilibrium Test was conducted to determine the effectiveness of SBMC in adsorbing heavy metals (Pb2+, Cu2+, Co2+, Cd2+, Ni2+, Zn2+). Results showed SBMC has a high percentage of fine grain size (silt 73-87% +clay 12-19 %), lower value of specific gravity (2.14-2.29), high liquid limit (79.50-84.00%), plasticity limit (49.18-59.35 %), plasticity index (20.15-34.22 %) and was categorized at very high plasticity in plasticity indexed chart. The SBMC also has maximum dry density value (1.36-1.37 g/cm3), optimum moisture content, wopt (34.55-37.97 %) and average hydraulic conductivity (6.35 x 10-7 - 6.88 x 10-7 m/s). The chemical properties of the SBMC1 showed it has a high pH value (6.95-7.42), organic matter (5.31-6.06 %), CEC (91.25-92.32 meq/100g), and SSA value (60.28-62.38 m2/g). The XRD results showed that kaolinite, and illite were the most prevalent clay minerals, with quartz as the non-clay mineral. SEM analysis also revealed that kaolinite and microfossils were within the SBMC. The Batch Equilibrium test also showed that SBMC in single solution exhibited higher sorption for Cu (Kd= 0.4499 L/g, R2=0.98), followed by Pb (Kd= 0.3701 L/g, R2=0.85), Co (Kd= 0.3232 L/g, R2= 0. 0.88), Ni (Kd= 0.1483 L/g, R2=0.98), Zn (Kd= 0.0711 L/g, R2= 0.93) and Cd (Kd= 0.0627 L/g, R2= 0.98). Based on physico-chemical, mineralogy and morphology results, SBMC is an excellent choice acting as natural clay-based energy material to be used as an engineered clay liner in a landfill area. Int. J. of GEOMATE. All rights reserved, including the making of copies unless permission is obtained from the copyright proprietors.